Randomized trial of transcutaneous auricular vagus nerve stimulation on patients with disorders of consciousness: A study protocol - Cheng, Lijuan; Sun, Lingxiu; Xu, Lu; Zhao, Falin; Liu, Xiaochen; Wang, Anqi; Di, Haibo; Cong, Yu-Sheng (Frontiers in Neurology, 2023)
Background Transcutaneous auricular vagus nerve stimulation (taVNS) has recently been explored for the treatment of Disorders of consciousness (DoC) caused by traumatic brain injury. The evidence of taVNS during the consciousness recovery has been recently reported. However, the mechanism of taVNS in the recovery of consciousness is not clear. This study attempts to investigate the effectiveness of taVNS in DoC by means of Coma Recovery Scale-Revised (CRS-R), Magnetic resonance imaging (MRI), Electrophysiology (EEG), and Single-molecular array (Simoa). Methods/design Nighty patients with DoC acquired brain injury are randomized into one of three groups receiving sham taVNS or active taVNS (just left and left or right), respectively. Each of the three groups will experience a 40 days cycle (every 10 days for a small period, baseline 2 weeks, intervention 2 weeks, 40 min per day, 5 days per week, then no intervention for 2 weeks, intervention 2 weeks, 40 min per day, and 5 days per week). Primary outcomes (CRS-R) will be recorded five times during every period. Secondary outcomes will be recorded at the first and at the last period [MRI, EEG, Phosphorylated tau (P-tau), and Neurofilament light chain (NFL)]. We will take notes the adverse events and untoward effects during all cycles. Discussion Transcutaneous auricular vagus nerve stimulation as a painless, non-invasive, easily applied, and effective therapy was applied for treatment of patients with depression and epilepsy several decades ago. Recent progress showed that taVNS has behavioral effects in the consciousness recovery. However, there is no clinical evidence to support the effects of taVNS on brain activity. Therefore, we will design a randomized controlled trial to evaluate the effectiveness and safety of taVNS therapy for DoC, and explore neural anatomy correlated to taVNS during the consciousness recovery. Finally, this protocol also tests some biomarkers along with the recovery of consciousness. Clinical Trial Registration Chinese Clinical Trial Registry, ChiCTR2100045161. Registered on 9 April 2021.